RANCANG BANGUN SISTEM PEMBELAJARAN E-LEANING BERBASIS WEBSITE PADA SMA NEGERI 8 KOTA TANGERANG SELATAN - Dania Silvani (2021)
SMA Negeri 8 Kota Tangerang Selatan is one of the senior secondary education institutions located in South Tangerang City. In the process of teaching and learning activities, SMA Negeri 8 Kota Tangerang Selatan does not yet have a media for students to obtain information about the teaching and learning process such as downloading teaching materials files, uploading assignment files, discussion forums, and other things related to the teaching and learning process online through the application e-learning website based. This raises a problem that causes students to have difficulty obtaining knowledge and teachers in providing learning material, if the teaching and learning process cannot be done directly or face-to-face, especially at this time due to the COVID-19 pandemic which impacts learning must be done at a distance far, it requires a website-based e-learning system. Making this system using the PHP programming language and MySQL database. The system development method used is a prototyping method that has stages, namely identifying the needs of system users, developing prototypes, evaluating prototypes, coding systems, testing systems, evaluating systems, and implementing systems. The results of this study are a website-based e-learning learning system with the main features for administrators to manage users, manage classes, manage subjects, and manage relationships. For teachers, managing material includes viewing a list of students who have not accessed the material, managing assignments including collection slots and grades, managing multiple choice quizzes with random questions for each student, and joining live chat. For students, access material, access assignments, view grades, access quizzes, join live chat, and email notifications. With the hope of helping the school both teachers and students in the teaching and learning process.